Causality of immune cells on primary sclerosing cholangitis: a bidirectional two-sample Mendelian randomization study - Wu, Pu; Xie, Sinan; Cai, Yunshi; Liu, Hu; Lv, Yinghao; Yang, Ying; He, Yucheng; Yin, Bangjie; Lan, Tian; Wu, Hong (Frontiers in Immunology, 2024)
Background: Observational studies have indicated that immune dysregulation in primary sclerosing cholangitis (PSC) primarily involves intestinal-derived immune cells. However, the causal relationship between peripheral blood immune cells and PSC remains insufficiently understood.A bidirectional two-sample Mendelian randomization (MR) analysis was implemented to determine the causal effect between PBC and 731 immune cells. All datasets were extracted from publicly available genetic database. The standard inverse variance weighted (IVW) method was selected as the main method for the causality analysis. Cochran's Q statistics and MR-Egger intercept were performed to evaluate the heterogeneity and pleiotropy.In forward MR analysis, the expression ratios of CD11c on CD62L+ myeloid DC (OR = 1.136, 95% CI = 1.032-1.250, P = 0.009) and CD62L-myeloid DC AC (OR = 1.267, 95% CI = 1.086-1.477, P = 0.003) were correlated with a higher risk of PSC.Each one standard deviation increase of CD28 on resting Treg (OR = 0.724, 95% CI = 0.630-0.833, P < 0.001) and CD3 on secreting Treg (OR = 0.893, 95% CI = 0.823-0.969, P = 0.007) negatively associated with the risk of PSC. In reverse MR analysis, PSC were identified with genetic causal effect on EM CD8+ T cell AC, CD8+ T cell AC, CD28-CD127-CD25++ CD8+ T cell AC, CD28-CD25++ CD8+ T cell AC, CD28-CD8+ T cell/CD8+ T cell, CD28-CD8+ T cell AC, CD45 RA-CD28-CD8+ T cell AC.Our study indicated the evidence of causal effects between PSC and immune cells, which may provide a potential foundation for future diagnosis and treatment of PSC.